Analysing the Multidimensional Nature of Poverty: a Focus on Housing Insecurity in South Africa - Zamokuhle Ndaba; Steven Henry Dunga; Precious Mncayi-Makhanya (International Journal of Business and Development Studies)
Housing satisfies crucial needs, as shown in Maslow’s Hierarchy of Needs. Be that as it may, the Sustainable Development Goals evidently have one critical aspect missing in its 17 goals: achieving housing security for all. Goal 11 mentions urban settlement but fails to understand the concept of housing security. Over a billion people reside in slums and other informal settlements across the globe, and the number is expected to increase. However, there is a lack of a comprehensive, multidimensional, and validated instrument for measuring the extent of housing insecurity despite housing significantly impacting household’s health, economic, and psychological well-being.Methods: This study sought to apply and adopt a newly developed multidimensional household housing insecurity index (HHII), consisting of eight dimensions that respond to the lack of universally accepted measures of housing insecurity. This study used primary data with a sample size of 600 South African households collected in four types of areas in two provinces (Gauteng and KwaZulu Natal). Results: The findings indicated that merely 25% of households were deemed housing secure, in stark contrast to 75% facing varying levels of housing insecurity, from mild to severe. This concerning result highlights that, even after more than thirty years of democracy, housing remains a significant problem in South Africa.Conclusions: The study reveals that housing insecurity significantly impacts Black populations, with female heads of households in rural and informal settings facing the most severe challenges.